The effect of family attitudes and preparation of high school entrance exam on habitual physical activity in children - AGOPYAN, ANİ; KÜÇÜK YETGİN, MERAL; PINAR, SALİH; PINAR, YELİZ (ELSEVIER SCIENCE BV, 2014)
Physical activity level (PAL) is an important factor to promote and maintain a healthy lifestyle along the whole life cycle. The children and adolescent period is the critical time to acquire positive lifestyle habits. The purpose of this study was to investigate the effect of both high school entrance exam (HSEE) and parental behaviors on habitual PAL of students during the preparation of this exam. Totally 319 Elementary School students (154 girls, 165 boys) between ages of 11-13 were selected randomly for this study. PAL of students were evaluated by using the Beacke Physical Activity Questionnaires. There were a no significant differences between attendance and non attendance to extra courses for HSEE in terms of word activity (WA), sport activity (SA), and leisure activity (LA) scores (p<.05) among the students. It was shown that regular physical activity attendance of mothers plaid a significant role in LA scores (p <=.03) among the students. However, WA, and SA scores of students were not affected from their mother's habitual activities (p<.05). On the other hand, there were significant differences in WA, and SA according to father's regular physical activity attendance (p <=.01). As a conclusion, parental habitual physical activity level played an important role in high score of student's LA. It is recommended to monitor and promote parental physical activity. (C) 2013 The Authors. Published by Elsevier Ltd.
Keywords: Sport activity; leisure activity; work activity; children; YOUTH